Pemberdayaan Kelompok PKK dalam Pengolahan Ubi Kayu Menjadi Frozen Cassava di Kabupaten Maros - Andi Ralle; St Sabahannur; Fariza Dhaifina Amran (Jurnal BALIRESO, 2026)
This 2025 Flagship Community Service (PKM) aims to empower 31 members of the PKK Group in Temmapadduae Village, Marusu District, Maros Regency, by processing cassava into frozen cassava as a shelf-stable food innovation to support food security and women's home businesses in rural areas of South Sulawesi. The implementation approach involves socialization, nutritional presentations, demonstrations, and hands-on training during August-November 2025, with stages of boiling sliced cassava (5 cm) in a mixture of seasoned coconut milk (10 g salt, 20 g garlic per liter), hygienic food-grade packaging, and freezing at -15Â°C to -25Â°C for 24 hours for 3 months shelf life without loss of nutritional value or crispiness. Achievements include 100% full engagement, 100% satisfaction level (Strongly Agree + Agree Likert scale), 100% progress in knowledge and skills, as well as 85% of participants being able to process independently after the session, which cuts harvest waste by 50% and has the opportunity to increase household income by 50% through marketing ready-to-fry snacks. The social effects consist of strengthening women, alternative food variations, and transforming the image of cassava from conventional processing to a modern product. The conclusion highlights the importance of innovation for the village economy, accompanied by continuous monitoring input and stakeholder partnerships for further development.